2017
DOI: 10.3390/app7020113
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Physical and Physiological Parameters in Simulated Particle Transport in the Alveolar Zone of the Human Lung

Abstract: Abstract:The trajectory and deposition efficiency of micron-sized (1-5 µm) particles, inhaled into the pulmonary system, are accurately determined with the aid of a newly developed model and modified simulation techniques. This alveolar model, which has a simple but physiologically appropriate geometry, and the utilized fluid structure interaction (FSI) methods permit the precise simulation of tissue wall deformation and particle fluid interactions. The relation between tissue movement and airflow in the alveo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Similar findings were reported in several subsequent studies [4,[13][14][15][16]. However, different findings of the alveolar flows were reported from different modeling studies [17][18][19][20][21][22][23][24]. These studies found a spiral type of vortex in the symmetry place of the alveoli.…”
Section: Introductionsupporting
confidence: 87%
“…Similar findings were reported in several subsequent studies [4,[13][14][15][16]. However, different findings of the alveolar flows were reported from different modeling studies [17][18][19][20][21][22][23][24]. These studies found a spiral type of vortex in the symmetry place of the alveoli.…”
Section: Introductionsupporting
confidence: 87%
“…In this study, the particle transport and deposition in different breathing scenarios such as light (15 l/min), normal (30 l/min), and heavy (60 l/min) breathing conditions were numerically investigated. The computer simulation results have been validated with the numerical results of Darquenne et al 13 and Ciloglu et al 36 for an alveolar duct model (G18), the flow rate of 30 l/min (not including expiration), and particles with diameter between 1 µ m and 5 μ m. Figure 2 shows the comparison of the particle deposition fractions as a function of particle diameter in the acinar region. As seen in Fig.…”
Section: Resultsmentioning
confidence: 82%
“…Recently, digital images have been used to construct an alveolar model and found that alveolar topology structure is highly irregular [159]. There are only a few studies [160][161][162] that performed numerical investigation of particle deposition in the alveolar region of human lung. The simplified numerical model of Talaat and Xi [160] demonstrates that alveolar structure and particle diameter effects on airflow and deposition.…”
Section: Alveolar Regionmentioning
confidence: 99%